2013
DOI: 10.1080/02786826.2013.865833
|View full text |Cite
|
Sign up to set email alerts
|

Performance of CHROMagar VRE Medium for the Detection of Airborne Vancomycin-Resistant/SensitiveEnterococcusSpecies

Abstract: Vancomycin-sensitive and vancomycin-resistant Enterococcus (VSE and VRE) species have become a significant health problem. CHROMagar medium, which permits direct, color-based identification of target pathogens, could potentially be used to rapidly monitor airborne VSE and VRE. In this study, the efficiency of CHROMagar VRE medium without vancomycin supplementation (CVSE) for collecting airborne vancomycin-sensitive Enterococcus faecalis was evaluated in a chamber study. Subsequently, the performance of bioaero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The Andersen 1‐STG impactor has a very similar air velocity to that of CFCs, at 23.3 m/s . However, our previous studies demonstrated that the culturable collection efficiency of the Andersen 1‐STG impactor was at least 10 times higher than that of CFCs when sampling for the same bacterial species . These results indicated that even though these air sampling velocities are similar, additional sampling stresses such as desiccation and filter elution caused by CFC sampling cause microbes to significantly lose their culturability.…”
Section: Discussionmentioning
confidence: 94%
“…The Andersen 1‐STG impactor has a very similar air velocity to that of CFCs, at 23.3 m/s . However, our previous studies demonstrated that the culturable collection efficiency of the Andersen 1‐STG impactor was at least 10 times higher than that of CFCs when sampling for the same bacterial species . These results indicated that even though these air sampling velocities are similar, additional sampling stresses such as desiccation and filter elution caused by CFC sampling cause microbes to significantly lose their culturability.…”
Section: Discussionmentioning
confidence: 94%
“…In field applications, higher sampling flow rates are needed to detect airborne microbe species present at low concentrations. Although sampling with a Nuclepore filter sampler at 20 l/min was not optimized, it has been used to monitor airborne Mycobacterium tuberculosis (Chen and Li, ), S. aureus (Hsiao et al., ), Enterococcus (Hsiao et al., ), and viruses (Tseng et al., ) in the field. For the Nuclepore filter sampler, the lower CR and VR values compared to impingement sampling reflect the loss of microbial culturability and viability during the sampling processes.…”
Section: Resultsmentioning
confidence: 99%
“…The purpose of this study was to optimize PMA‐qPCR for detecting viable A. baumannii and subsequently to evaluate the effects of three bioaerosol sampling methods (the AGI‐30 impinger, BioSampler and Nuclepore filter sampler) on A. baumannii recovery by culture, qPCR, and PMA‐qPCR. Based on our experience, relative humidity (RH) may affect the biological efficiency of the samplers when collecting viruses and gram‐positive bacteria (Hsiao et al., , ; Tseng and Li, ). Therefore, airborne samples were taken at three different RH levels (35%, 55%, and 85% RH).…”
Section: Introductionmentioning
confidence: 99%
“…The challenged bacterial aerosols in this study were Acinetobacter baumannii, Enterococcus faecalis, and Staphylococcus aureus. These bacterial species are highly related to nosocomial infection and can cause airborne dispersal and transmission (Hsiao et al 2012;Hsiao et al 2014;Tseng et al 2015). The predecontamination effects of GS5 were studied and divided into two aspects.…”
Section: Introductionmentioning
confidence: 99%